Proses Kreatif Drama Untuk Meningkatkan Keterampilan Berbicara Mahasiswa BIPA - Primadi, Tedi; Nurlina, Laily (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Cases were found where BIPA students studying in Indonesia did not have good language skills, especially in the speaking aspect. Meanwhile, speaking skills are one of the main skills in communication that are most often used in everyday life. For this reason, BIPA students' speaking skills need to be improved. Drama games are elementally close to communication. Because in drama games language is used to convey stories to the audience. This research aims to determine the effectiveness of the drama creative process in improving BIPA students' speaking skills. This research uses descriptive qualitative methods. The approach used is literature study. Data is collected through sources that are considered relevant, such as books, articles and other sources in the last ten years. The results of this research are that drama games have content that is closely related to aspects contained in speaking skills, both from a verbal perspective which includes intonation, articulation and power and from a non-verbal perspective, namely gestural and facial expressions. his speaking skills. Based on research findings and previous research results, drama is known to improve speaking skills.